In connection with the V centenary of the Complutensian Polyglot Bible's Greek column - Gil Fernández, Luis (Cuadernos de Filología Clásica. Estudios griegos e indoeuropeos, 2015)
The non-negligible volume of research subsequent to Delitzsch (1886) has removed long-standing prejudices and granted the CPB its true value not only as editio princeps of the Septuagint and the New Testament, but also as textual witness. It is no longer believed that the Complutensian publishers adapted the Greek text to the Vulgata’s or the Latin to the Hebraica veritas, or that they resorted to Rückübersetzungen (‘back-translations’) from Latin into Greek for those passages that did no exist in the latter language (the so-called Spanish Greek). The ‘solitary’ readings of the CPB have considerably diminished once discovered that they featured, for instance, in the III century Washingtonian papyrus or in Ezekiel’s papyrus (II-III centuries), imposing the conclusion that Alcala’s humanists used manuscripts unknown to us and attesting to the CPB’s merits as textual witness.
Keywords: Biblical text criticism; Septuagint; Greek New Testament; history of editions.